2006
DOI: 10.1007/s00464-005-0450-9
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal hand-assisted laparoscopic surgery for endoscopic adrenalectomy

Abstract: Although hand-assisted laparoscopic surgery (HALS) is very common in various laparoscopic procedures, it is rarely used for retroperitoneal endoscopic adrenalectomy because of the small working area. The authors evaluate HALS in endoscopic adrenalectomy with respect to its use as a rescue procedure in complicated cases. In their department, 47 patients underwent endoscopic adrenalectomies between 1998 and 2004. Mainly because of complicated anatomy, three primary aldosteronism cases were converted to retroperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Definitive treatment of any pheochromocytoma is surgical excision. Studies also have shown laparoscopic resection of large adrenal tumors to be safe [ 11 ]. The resection of our dopamine secreting pheochromocytoma was completed with robotic assisted laparoscopic adrenalectomy without complication.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive treatment of any pheochromocytoma is surgical excision. Studies also have shown laparoscopic resection of large adrenal tumors to be safe [ 11 ]. The resection of our dopamine secreting pheochromocytoma was completed with robotic assisted laparoscopic adrenalectomy without complication.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery is considered the standard surgical option. Hand-assisted laparoscopic surgery has been adapted for the removal of large tumors and for the rescue of operative procedures in complicated cases of laparoscopic surgery [9]. …”
Section: Discussionmentioning
confidence: 99%
“…An LA was performed using the standard lateral retroperitoneal approach. 21 The tumor was located in the inferior part of the left adrenal gland. The left superior adrenal artery, two branches of the left inferior adrenal artery, and the left adrenal vein (central vein) observed in the inferior part of the gland were dissected and ligated with clips.…”
Section: Case Reportmentioning
confidence: 99%